Car suspension control system based on wireless power transmission technologies - Грецких, Д.В.; Лихограй, В.Г.; Щербина, А.А.; Сакало, С.Н.; Ткачева, Т.С. (Radiotekhnika, 2020)
The paper discusses the features of building intelligent wireless sensor networks (WSN) and alternative ways to power their nodes. The rapid development of WSN contributes to the successful practical implementation of relevant and demanded communication technologies to support a new quality of the exchange of information, services, services and applications. When solving various practical problems, WSN devices can work in conditions when replacing the batteries is inconvenient or even impossible. For this reason, alternative energy sources can be an effective solution to address the above disadvantages, which in some cases hamper the practical implementation of WSN. The paper proposes the concept of a car suspension control system (CSCS), implemented on a component basis of WSN. At the same time, the features of constructing such a system are considered and the rationale for the technical implementation of its functional elements is carried out. It is proposed to transmit data on the state of the suspension to the on-board computer of the car over the air; power supply of the CSCS itself is carried out using a wireless energy transfer system (WPT). For this, the features of energy extraction from the environment (EH – Energy Harvesting) are considered and at this stage the low efficiency of this approach is shown. The way out of this situation for the power supply of the CSCS is the use of radio frequency energy transfer. Sketch calculations of the power consumption of the control panel and the required level of microwave power of the transmitter of the wireless energy transmission system were carried out. For the practical implementation of CSCS and their serial production, it is necessary to carry out a number of additional studies related to the fact that the underbody of the car and its individual parts participate in the formation of the emitted (received) antenna of the electromagnetic field and therefore affect the characteristics of the rectenna subsystem of the WPT and the antennas of the subsystem data transmission. Knowing the laws of this influence is necessary both in the development of antennas and in determining the optimal places for their installation on the underbody of a car. Therefore, the exact determination of the field components, the calculation of the electrical characteristics of the antennas taking into account the influence exerted on them and the evaluation of the characteristics of the system itself is possible only on the basis of a strict electrodynamic approach.